2021
DOI: 10.1029/2021gl094808
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Rock Magnetic and Meteorological Investigation of the Precipitation Boundary Across the Tibetan Plateau

Abstract: The Tibetan Plateau (TP) and its adjacent areas are located in the transitional zone of the high and cold mountainous regions, monsoonal humid regions, and arid regions of Central Asia. The TP is the highest plateau on Earth, with a complex terrain of plateaus, broad basins, high mountains, arid deserts and lakes. Due to its unique geographical location, the TP is influenced by the East Asian and Indian summer monsoons, and the Westerlies circulation (Chen et al., 2019;Machalett et al., 2008). Characterizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Studies on surface soil samples have found a positive correlation between pedogenic magnetite/maghemite content and MAP in the TP and its adjacent areas (Ning et al., 2021; Zan et al., 2020). A preliminary magnetic susceptibility study of modern topsoil in the WSP has revealed a close relationship between χ fd % and precipitation (H. Chen et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on surface soil samples have found a positive correlation between pedogenic magnetite/maghemite content and MAP in the TP and its adjacent areas (Ning et al., 2021; Zan et al., 2020). A preliminary magnetic susceptibility study of modern topsoil in the WSP has revealed a close relationship between χ fd % and precipitation (H. Chen et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of ultrafine magnetite precipitates depends on the drying‐wetting cycles and the average moisture of the soil, which is used to define the magnetite enhancement proxy (Orgeira et al., 2011). Modern soil magnetic studies on the Chinese Loess Plateau (CLP) and its adjacent areas have found that the pedogenic ferromagnetic minerals are closely related to precipitation (Gao et al., 2018; Ning et al., 2021; Song et al., 2014).…”
Section: Introductionmentioning
confidence: 99%